1988
DOI: 10.1093/ije/17.3.643
|View full text |Cite
|
Sign up to set email alerts
|

The Transmission Potential of Monkeypox Virus in Human Populations

Abstract: Data on monkeypox in Zaire over the five years 1980-1984 are analysed to assess the protection imparted by past smallpox vaccination and the transmission potential of the virus in unvaccinated communities. Attack rates in individuals with and without vaccination scars indicated that smallpox vaccination (discontinued in 1980) imparted approximately 85% protection against monkeypox. It is predicted that monkeypox virus will continue to be introduced into human communities from animal sources, and that the avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
483
1
12

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 532 publications
(507 citation statements)
references
References 0 publications
11
483
1
12
Order By: Relevance
“…Fenner et al [4] acknowledged that there was natural concern about the vacated smallpox niche when monkeypox virus was first discovered to infect humans in Africa in 1970. They then reviewed subsequent genetic and epidemiological evidence, showing that monkeypox is not a direct ancestor of smallpox and transmissibility among humans had been concluded to be too low to allow establishment in human populations [23]. (These arguments run parallel to those cited by Breman & Henderson [6] in dismissing any imminent risk from monkeypox.)…”
Section: Roots Of the Controversy: The Case Against Nichesmentioning
confidence: 99%
See 1 more Smart Citation
“…Fenner et al [4] acknowledged that there was natural concern about the vacated smallpox niche when monkeypox virus was first discovered to infect humans in Africa in 1970. They then reviewed subsequent genetic and epidemiological evidence, showing that monkeypox is not a direct ancestor of smallpox and transmissibility among humans had been concluded to be too low to allow establishment in human populations [23]. (These arguments run parallel to those cited by Breman & Henderson [6] in dismissing any imminent risk from monkeypox.)…”
Section: Roots Of the Controversy: The Case Against Nichesmentioning
confidence: 99%
“…In a pioneering analysis, Jezek et al [48] extrapolated their findings to show that-if nothing changed except the proportion vaccinated in the population-monkeypox would not establish sustained transmission among humans. A follow-up article re-stated this finding in terms of the basic reproductive number, reporting that R 0 for monkeypox in an unvaccinated population (in rural DRC) was approximately 0.83, less than the threshold value of 1 needed for persistent circulation [23]. This conclusion influenced the decision to cease intensified surveillance for monkeypox and maintain the cessation of smallpox vaccination.…”
Section: (D) Revisiting the Critiquesmentioning
confidence: 99%
“…In humans, MPXV and variola virus have similar asymptomatic incubation periods ranging from 7-17 days followed by development of generalized rash. However, smallpox had a much higher secondary attack rate (25-96 %) than monkeypox (5-11 %) (Arita & Gromyko, 1982;Fine et al, 1988). Previous studies defined two distinct MPXV clades, West African and Congo Basin, with unique disease manifestations (Chen et al, 2005;Likos et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Survey showed that 85% immunity against monkey pox comes from the small pox vaccination but human only caught infection by having contact with infected animals and there is no transmission of infection from human to human because viruse is not capable of surviving in human if vaccination is absent (Fine et al, 1988). Now monkey pox is able to survive in humans due to genetic changes (gene loss) and human to human transmission is possible.…”
Section: Inter Human Transmissionmentioning
confidence: 99%